2005
DOI: 10.1364/josab.22.000088
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence of rubidium in a submicrometer vapor cell: spectral resolution of atomic transitions between Zeeman sublevels in a moderate magnetic field

Abstract: It is experimentally demonstrated that use of an extremely thin cell (ETC) with the thickness of a Rb atomic vapor column of ϳ400 nm allows one to resolve a large number of individual transitions between Zeeman sublevels of the D 1 line of 87 Rb and 85 Rb in the sub-Doppler fluorescence excitation spectra in an external magnetic field of ϳ200 G. It is revealed that due to the peculiarities of the Zeeman effect for different hyperfine levels of Rb, all allowed transitions between magnetic sublevels can be clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
3

Relationship

6
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…To calculate it one must have the matrix elements for theÎĴ operator, see Eq. (6). Taking into account, that according to the cosine law…”
Section: Theoretical Modelmentioning
confidence: 99%
“…To calculate it one must have the matrix elements for theÎĴ operator, see Eq. (6). Taking into account, that according to the cosine law…”
Section: Theoretical Modelmentioning
confidence: 99%
“…We need to guarantee the possibility of photon loss. The explosion can be amplified to the classical level, if desired, using fluorescence detection to observe whether the |r state is occupied or not [44,45]. This last step is optional.…”
Section: Quantum Bombs With Rydberg Atomsmentioning
confidence: 99%
“…As this takes place, the probabilities of atomic transitions usually change significantly as well [5][6][7] . Previous papers [8][9][10][11] demonstrated that the use of resonance fluorescence spectra of a STC filled with atomic vapor and of thickness L = 0.5λ (where λ = 794 nm (or 780 nm) is the wavelength of the laser radiation whose frequency is resonant with the atomic transition of the D 1,2 lines of Rb) allows one to separate and study atomic transitions between the levels of the hyperfine structure of the D 1,2 lines of 87 Rb atoms in magnetic fields with B varying in the range of 10 -200 G. The achieved high sub-Doppler spectral resolution is caused by the effect of a strong narrowing of the fluorescence spectrum of a nanocell with the atomic vapor column thickness L = 0.5λ (the method was called HLZM) compared to normal 1cm-long cells (for which the Doppler width is ~ 500 MHz). It is known that, with the saturated absorption (SA) technique, the sub-Doppler spectral resolution can also be achieved using cm-long cells (when the parameters are properly chosen, it is possible to obtain peaks of reduced absorption with a width close to the natural one ~ 6 MHz).…”
Section: Introductionmentioning
confidence: 99%